The Effect of Heating Pillow Therapy on Chest Pain Intensity in Patients with Acute Coronary Syndrome (ACS) at Dr. H. Moch Ansari Saleh Hospital - Aldi, Muhamad; Mohtar, M. Sobirin; Gaghauna, Eirene E. M.; Santoso, Bagus Rahmat (Journal of Nursing Science Update (JNSU), 2025)
Acute Coronary Syndrome (ACS) represents a category of cardiovascular disease characterized by typical symptoms, particularly chest pain, resulting from the narrowing and blockage of the coronary arteries. This study investigates the effects of heating pad therapy on the intensity of chest pain in patients diagnosed with Acute Coronary Syndrome at the Dr. H. Moch Ansari Saleh Regional Hospital in Banjarmasin. The research employed a quasi-experimental design utilizing a one-group pretest-posttest approach. Sampling was conducted using purposive sampling techniques, resulting in a sample size of 30 respondents. Data collection instruments included standard operating procedures for thermotherapy, the Numeric Rating Scale, and pain observation sheets. The Wilcoxon analysis test was utilized for data analysis. Findings indicated that before the administration of Heating Pad Therapy, a majority of respondents reported experiencing moderate pain (4-6), accounting for 60%. Following treatment, the majority reported experiencing mild pain (1-3), comprising 76.7% of the sample. The statistical analysis yielded a p-value of 0.001. Consequently, the study concludes that Warm Pillow Therapy has a significant influence on the intensity of chest pain in patients with Acute Coronary Syndrome at Dr. H. Moch Ansari Saleh Regional Hospital.